Primary prevention of atherosclerosis by pretreatment of low-density lipoprotein receptor knockout mice with sesame oil and its aqueous components - Aluganti Narasimhulu, Chandrakala (Sci Rep, 2018)
Pharmacological intervention using statins and PCSK9 inhibitors have become first-line therapy in the prevention of hypercholesterolemia and atherosclerosis. Currently, no agent is available for the primary prevention of atherosclerosis. However, there is an emerging hypothesis that atherosclerosis could be driven by inflammation. In this study, we tested whether pretreatment with an aqueous extract from sesame oil (SOAE), which showed potent anti-inflammatory properties without hypocholesterolemic actions, would prevent subsequent atherosclerosis development in a mouse model. RAW 264.7 macrophages and female low-density lipoprotein receptor knockout (LDLR(−/−)) mice were used for in vitro and in vivo studies, respectively. Plasma lipids, cytokines and atherosclerotic lesions were quantified at the end of the study. RNA was extracted from the liver and aortic tissues and used for gene analysis. Pre-treatment of SOAE prevented Ox-LDL uptake by RAW macrophages and further inflammation in vitro. SOAE pre-treatment significantly reduced atherosclerotic lesions and pro-inflammatory gene expressions in LDLR(−/−) mice as compared to control mice. No significant change in plasma cholesterol levels was observed. A significant reduction in plasma levels of TNF-α, IL-6, MCP-1 and VCAM1 was observed in the SOAE pre-treated animals. This is the first study that demonstrates that pre-treatment with anti-inflammatory agents, could delay/decrease atherosclerosis.